Perencanaan Enterprise Architecture Pelayanan Informasi Meteorologi Klimatologi dan Geofisika - Krismadinata, Krismadinata; Minangsih, Maya; Yahfizham, Yahfizham; Verawardina, Unung (Universitas Diponegoro, 2020)
The importance of the research was carried out because of the increasing public demand for Information and Communication Technology (ICT) assisted information system services at the Meteorology, Climatology and Geophysics Agency (BMKG). The expansion aims to be done with the concept of Enterprise Architecture (EA) which includes the pattern of The Open Group Architecture Framework (TOGAF) which has provided Architecture Development Method (ADM). The method approach used is design research which includes service concepts, architectural design, and the feasibility blueprint for computer-aided information systems in the future. The instrument used was through observation sheets, interview guides and documentation to gather planning information, and using a product questionnaire involving 5 experts consisting of 3 ICT lecturers and 2 business managers, while the practicality test involved 5 respondents. The study took place in BMKG Padang Panjang, West Sumatra Province, from June to September 2019. The data analysis technique in this study used descriptive analysis techniques. This study has produced a design that meets the criteria set out by the standard validity and practicality tests. Based on the results of tests conducted by experts (validator), it was found that the information system service blueprint was feasible to be built with 92% and 82% acceptance of the very valid category in the very practical category. because it is proven valid and practical.